Does Financial Technology Increase The Efficiency of Zakat Management Organizations or Other Factors? - Aziz, Roikhan Mochamad; Hidayat, M Fahmi; Salsabila, Fauziyah Latiefa (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2023)
The purpose of this research is to analyze the efficiency of Zakat Management Organizations (ZMO) in utilizing financial technology to increase the collection and distribution of Zakat. Data was obtained from 4 social finance organizations that utilize financial technology: National Amil Zakat Agency (NAZA), Nahdathul Ulama (NU Care), Dompet Dhuafa, and Rumah Zakat between 2018-2019. The methodology used an efficiency approach with the Data Envelopment Analysis (DEA) tool. Operational variables are total operating and socialization costs as input variables, while Zakat’s entire collection and distribution are the output variables. The results are the 4 ZMOs based on Financial Technology, such as NAZA, NU Care, Dompet Dhuafa, and Rumah Zakat, indicate that NU Care is the most efficient ZMO with a score of 1.00 throughout 2018-2019 because it can decrease input costs and optimize output due to its large mass base and volunteer programs up to the village level. Meanwhile, other ZMOs experience inefficiency with a score below 0.60, which occurs due to the use of disproportionate inputs and outputs due to ZMOs having multiple roles and a relatively equal ZMO donor base, which causes competition among ZMOs. Hahslm Analysis proves that optimizing ZMO input and output is by using resources in a balanced way by minimizing costs and maximizing income, which is an important factor outside financial technology.